The Relationship between Sensory Learning and Recalling Styles and Speaking Proficiency: A Case Study of Yemeni EFL University Students - Al-Showthabi, AbdulRahim Ali; Al-Mekhlafi, Mohammed Abdo Ahmed; Alghamri, Safiah Jobran (Journal of Educational and Psychological Sciences, 2025)
This quantitative correlational study addressed the relationship between sensory learning and recalling styles and speaking proficiency. The study sample consisted of 105 (9 male and 96 female) students enrolled in the English Departments for the academic year 2022-2023. Sensory learning and recalling style questionnaires and speaking proficiency test were used. The two instruments’ validity and reliability have been verified. The study results showed that there is a statistically significant relationship between the sensory (auditory) learning style and speaking proficiency (r = 0.392, p < 0.01); There is also a weak, non-statistically significant relationship between the sensory (visual) learning style and English speaking proficiency(r =0.008, p< 0.467).The study, then again, revealed, negative non-significant relationship between sensory recalling (visualization speech) and speaking proficiency (r =-0.069, p < 0.241). It also revealed a statistically significant and strong relationship between sensory recalling (verbalization speech) and speaking proficiency (r = 0.699, p < 0.01). The results of the multiple regression analysis also revealed that the sensory learning style (auditory) together with the sensory recalling style (verbalization speech) explained 54.2% of the variance in speaking proficiency. The sensory recalling style (verbalization speech) alone explained 48.3% of the variance in the English-speaking proficiency. Beta coefficient indicated that sensory learning (auditory) and sensory recalling style (verbalization speech) predicted speaking proficiency. However, the sensory recalling style (verbalization speech) was the best predictor of the English-speaking proficiency, followed by the sensory (auditory) learning style.